Парламентська республіка: досвід Франції - Козинець, О.Г. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются предпосылки возникновения Четвертой республики во Франции, в частности формирование политической системы, образование Временного правительства, созыв Учредительного собрания и проведение референдумов, на которых решались вопросы дальнейшего государственного развития Франции. Характеризуются обстоятельства провозглашения Четвертой республики, форма ее правления и законодательное оформление. Особое внимание при этом отводится характеристике Конституции 1946 г., ее сравнению с Органическими законами Третьей республики 1875 г. The preconditions of the fourth Republic formation in prance, namely, the political system shaping, provisional government forming, constituent assembly convening and referendum conducting where the issues concerning the further government - legal development prance were solved. Also the circumstances of the Fourth Republic proclaiming are characterized the forms of its governing and the legislative formulating are analyzed in the article. A special attention is paid to the characteristics of the Constitution of France, 1946, its comparison with the Organic Laws of the Third Republic 1875.